Проблеми крайової керованості для рівняння коливання неоднорідної струни на півосі - Халіна, К.С. (Український математичний журнал, 2012)
Рассматривается волновое уравнение на полуоси: wtt(x,t)=wxx(x,t)—q(x)w(x,t),x>0. Это уравнение управляется одним из двух граничных условий:w(0,t)=u0(t) или wx(0,t)=u1(t),t∈(0,T), где u0,u1 — управления. В обоих случаях потенциал q удовлетворяет условию q ∈ q∈C[0,∞), управления принадлежат классу L∞ и время T> 0 фиксировано. Управляемые системы рассмотрены в пространствах Соболева. С помощью операторов, сопряженных к операторам преобразования для задачи Штурма – Лиувилля, получены необходимые и достаточные условия 0- и ε-управляемости для этих систем. Управления, решающие поставленные задачи, найдены в явном виде. We consider a wave equation on a semiaxis, namely, w t t (x,t) = w xx (x,t) - q(x)w(x,t), x>0. The equation is controlled by one of the following two boundary conditions w(0,t)=u 0(t) and w x (0,t)=u 1(t), t ∈ (0,T) where u 0 and u 1 are controls. In both cases, the potential q satisfies the condition q ∈ C[0,∞) the controls belong to the class L ∞; and the time T > 0 is fixed. These control systems are considered in Sobolev spaces. Using the operators adjoint to the transformation operators for the Sturm–Liouville problem, we obtain necessary and sufficient conditions for the null-controllability and approximate null-controllability of these systems. The controls that solve these problems are found in explicit form.